2002
DOI: 10.3758/bf03194729
|View full text |Cite
|
Sign up to set email alerts
|

Top-down gain control in the auditory system: Evidence from identification and discrimination experiments

Abstract: The influence of intensity range in auditory identification and intensity discrimination experiments is well documented and is usually attributed to nonsensory factors. Recent studies, however, have suggested that the stimulus range effect might be sensory in origin. To test this notion, in one set of experiments, we had listeners identify the individual tones in a set. One baseline condition consisted of identifying four 1-kHz, low-intensity tones; the other consisted of identifying four 1-kHz, high-intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(65 citation statements)
references
References 29 publications
6
57
2
Order By: Relevance
“…The results support a model in which the function of top-down contrast sensitivity control is to optimize performance while protecting against overload. In this regard, it is similar to the top-down control mechanism proposed by Parker et al (2002) for auditory intensity. We suggest that contrast sensitivity is controlled in a top-down manner in addition to bottom-up control.…”
Section: Top-down Control Over Low-level Visual Processesmentioning
confidence: 49%
See 2 more Smart Citations
“…The results support a model in which the function of top-down contrast sensitivity control is to optimize performance while protecting against overload. In this regard, it is similar to the top-down control mechanism proposed by Parker et al (2002) for auditory intensity. We suggest that contrast sensitivity is controlled in a top-down manner in addition to bottom-up control.…”
Section: Top-down Control Over Low-level Visual Processesmentioning
confidence: 49%
“…Here it has been suggested that the function of a nonlinear intensity control mechanism is to maximize discriminability and protect the auditory system from an overload. Specifically, Parker, Murphy, and Schneider (2002) showed that one function of auditory gain control, the auditory analogue of visual contrast sensitivity control, is to protect the auditory system from an intensity overload.…”
Section: Testing For a Top-down Influence Over Contrast Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…One discrepancy between the two observations concerns the role of listener expectancies. The reduction in identification accuracy was essentially eliminated when listeners were instructed to ignore a predictable loud tone, implying that the gain-control mechanism can be adjusted according to the experimental contingencies (Parker et al, 2002). In contrast, reduction of loudness usually occurs even when the listeners are instructed to ignore the inducer (Arieh & Marks, 2003b).…”
Section: Discussionmentioning
confidence: 99%
“…Loud transients have also been shown to affect identification and discrimination (Parker, Murphy, & Schneider, 2002). In one condition, listeners were instructed to identify four weak tones (e.g., 25,30,35,and 40 dB [SPL]), and in a second condition, a fifth tone, either 90 or 45 dB (SPL), was added to the stimulus set.…”
Section: Discussionmentioning
confidence: 99%